Analisis Hubungan Golongan Darah dan Kategori Usia Terhadap Kecepatan Lari Sprint Jarak Pendek - Arimbi; Arifuddin Usman; Poppy Elisano Arfanda; Sanrebayu; Wahyana Mujari Wahid (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Running speed is influenced by various physiological and biological factors, but empirical evidence regarding the role of simple genetic indicators such as blood type and age in young adults still shows mixed results. This study aims to analyze the relationship between blood type and age on running speed as an important component of physical performance. This study used a quantitative design with an observational analytical approach. The study subjects consisted of 129 respondents aged 20–32 years who were selected based on certain inclusion criteria. Blood type was determined through serological testing, while running speed was measured using a 60-meter dash test with a digital timer. Data analysis was performed using One-Way ANOVA and Kruskal–Wallis tests to examine differences in running speed based on blood type and age. The results showed that blood type had no significant relationship with running speed (p > 0.05), although there was variation in the mean between groups. Age also showed no significant relationship with running speed (p > 0.05), but there was a tendency for decreased performance in respondents aged over 30 years. These findings indicate that blood type and age in the young adult range are not dominant factors in determining running speed, so other factors such as training, physical condition, and lifestyle need to receive more attention in developing physical performance